Key drivers for adopting design build: A comparative study between project stakeholders - Lee, Z. P.; A. R., Rahimi; Doh, Shu Ing (Elsevier Ltd., 2020)
The construction industry recognizes the need for a relationship-based procurement by considering the stakeholders to promote the right project delivery method. Design-Build (D-B) is an alternative procurement method that can overcome the incompleteness of Design-Bid-Build(D-B-B) in delivering construction projects. D-B is becoming more common in the United States, China, and Japan, but numerous construction projects are still practicing D-B-B. Hence, understanding the drivers of D-B adoption among project stakeholders can determine the root cause for the acceptance or rejection of D-B. This study aims to compare the key drivers for D-Badoption among the three main stakeholders, namely client, consultant, and contractor. Toachieve that objective, this study analyzes survey data from 111 professionals with D-B project-related experiences. The results reveal sixteen D-B drivers that affect the stakeholders’ decision to adopt D-B. From the sixteen D-B drivers, the specific key D-B drivers for consultants are “interest in the design-build,” “reduce works variations,” and “better track record.” Conversely, “better project pricing” and “greater allocation of risks to contractors” are the specific key D-B drivers for clients and contractors, respectively. This study contributes to the existing literature on D-B by investigating the inter-relationships between D-B drivers of project stakeholders. The key D-B drivers can help researchers to formulate strategies to improve D-B adoption. The research findings could enhance the understanding of D-B drivers by providing a valuable reference for stakeholders to promote D-B in the construction industry.